1998
DOI: 10.1046/j.1471-4159.1998.71031151.x
|View full text |Cite
|
Sign up to set email alerts
|

Basement Membrane Proteins Influence Brain Capillary Endothelial Barrier Function In Vitro

Abstract: Abstract:The influence of basement membrane proteins on cellular barrier properties of primary cultures of porcine brain capillary endothelial cells grown on permeable filter inserts has been investigated. Measurements of transcellular electrical resistance (TEA) by impedance spectroscopy were performed with cells cultured on type IV collagen, fibronectin, laminin, and one-to-one mixtures of these proteins. Moreover, a one-to-one combination of type IV collagen and SPARC (secreted protein acidic and rich in cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(115 citation statements)
references
References 33 publications
3
112
0
Order By: Relevance
“…Such cell-matrix interactions can stimulate a number of intracellular signaling pathways (reviewed in Tilling et al, 2002). Matrix proteins can influence the expression of endothelial TJ proteins (Tilling et al, 1998;Savettieri et al, 2000), indicating that although the TJ constitute the primary impediment to paracellular diffusion, the proteins of the basal lamina are likely involved in their maintenance.…”
Section: The Extracellular Matrixmentioning
confidence: 99%
“…Such cell-matrix interactions can stimulate a number of intracellular signaling pathways (reviewed in Tilling et al, 2002). Matrix proteins can influence the expression of endothelial TJ proteins (Tilling et al, 1998;Savettieri et al, 2000), indicating that although the TJ constitute the primary impediment to paracellular diffusion, the proteins of the basal lamina are likely involved in their maintenance.…”
Section: The Extracellular Matrixmentioning
confidence: 99%
“…Collagens play critical roles in the CNS, for example, in maintaining the integrity of the blood-brain barrier (Tilling et al, 1998). However, the properties given to the tissue by the collagens are not restricted to their structural roles in the basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this aim different techniques have been recruited, e.g. utilizing of the hydrocortisone and serum free medium in order to increase the TEER (up to 1000 cm 2 ) by stimulating the formation of barrier properties (Hoheisel et al 1998). …”
Section: Bioelectrical Properties and Permeabilitymentioning
confidence: 99%
“…The ECs in general do not express their final destination-specific differentiated features until those features are induced by local environment-produced conditions including extracellular matrix. Using primary cultures of PBCECs, Tilling et al (1998) examined the effect of collagen IV, fibronectin, laminin and a secreted acidic protein and rich in cysteine alone or one-to-one mixtures of them. They showed that these proteins are involved in tight junction formation between cerebral capillary endothelial cells by presenting increased TEER (Robert & Robert, 1998;Tilling et al, 1998).…”
Section: Extracellular Matrixmentioning
confidence: 99%